Hubungan Pemberian Konseling oleh Petugas Kesehatan dengan Pemilihan Metode Kontrasepsi Jangka Panjang (MKJP) di Puskesmas Pakuan Baru - Ria Febrina (Jurnal Akademika Baiturrahim Jambi, 2021)
An increase in population can lead to poverty, economic inequality in the population which is usually measured by the proportion of households with income below the poverty line. One of the government's efforts to control the rate of population growth is through the implementation of a family planning program (KB) for fertile age couples age (PUS) using contraception. The use of long term contraception methods is still very low, of the total number of active family planning participants, only 17.45% of them use long term contraception methods. Meanwhile, 81.23% were non- long term contraception methods family planning users and 1.32% used traditional family planning. Jambi Province only 1.9% uses long term contraception method. Based on data obtained from the Jambi City Health Office in 2018 the number of IUD KB participants was 2,032, 1,252 implants, 542 MOW people, 16 MOP people from 20 community health center in Jambi City, Pakuan Baru community health center none of the active family planning participants which uses long term contraception method. This study was to determine the relationship of counseling by health workers with the choice of long-term contraceptive method at Pakuan Baru Community Health Center, Jambi City. This type of quantitative research with a descriptive design. Respondents who were active family planning participants who visited the Pakuan Baru community health center were taken using accidental sampling. The data collection technique was done by filling out a questionnaire. The data were processed using fisher exact statistical tests. The results of the study most of the respondents used long term contraception method of 24 (57.1%), there was a relationship between the provision of counseling and the choice of long term contraception method with a p-value: 0.001 and there was no relationship between the provision of counseling media by health workers and the selection of long term contraception method with a p-value: 0.068.